Deceptive vocal duets and multimodal display in a songbird. Issue 1864 (4th October 2017) - Ręk, Paweł; Magrath, Robert D.
Abstract : Many group-living animals cooperatively signal to defend resources, but what stops deceptive signalling to competitors about coalition strength? Cooperative-signalling species include mated pairs of birds that sing duets to defend their territory. Individuals of these species sometimes sing 'pseudo-duets' by mimicking their partner's contribution, but it is unknown if these songs are deceptive, or why duets are normally reliable. We studied pseudo-duets in Australian magpie-larks, Grallina cyanoleuca, and tested whether multimodal signalling constrains deception. Magpie-larks give antiphonal duets coordinated with a visual display, with each sex typically choosing a different song type within the duet. Individuals produced pseudo-duets almost exclusively during nesting when partners were apart, but the two song types were used in sequence rather than antiphonally. Strikingly, birds hid and gave no visual displays, implying deceptive suppression of information. Acoustic playbacks showed that pseudo-duets provoked the same response from residents as true duets, regardless of whether they were sequential or antiphonal, and stronger response than that to true duets consisting of a single song type. By contrast, experiments with robot models showed that songs accompanied by movements of two birds prompted stronger responses than songs accompanied by movements of one bird, irrespective of the number of song types or singers. We conclude that magpie-larks used deceptive pseudo-duets when partners were apart, and suppressed the visual display to maintain the subterfuge. We suggest that the visual component of many species' duets provides the most reliable information about the number of signallers and may have evolved to maintain honesty in duet communication.